Responses of switchgrass (panicum virgatum l.) to precipitation amount and temperature. - Hartman, Jeffrey C. (Kansas State University, 2011)
Anthropogenic climate change is likely to alter the function and composition of ecosystems worldwide through increased precipitation variability and temperatures. To predict ecosystem responses, a greater understanding of the physiological and growth responses of plants is required. Dominant species drive ecosystem responses, and it is essential to understand how they respond to understand potential ecosystem changes. Dominant species, such as switchgrass (Panicum virgatum L.), posses large genotypic and phenotypic variability, which will impact the degree of responses to projected climate changes. I studied the physiological and growth responses of switchgrass, a common perennial warm-season C4 grass that is native to the tallgrass prairie, to alterations in precipitation amount and temperature. The first experiment I conducted focused on the responses of three ecotypes of P. virgatum to three precipitation regimes (average, 25% below, 25% above). I concluded that the physiological responses of photosynthesis, stomatal conductance, transpiration, dark-adapted fluorescence, and mid-day water potential in P. virgatum were explained by ecotypic differences. Robust responses to altered precipitation were seen in the water use efficiency, mid-day water potential, and aboveground biomass. Ecotypic differences were also seen in several aboveground biomass variables, and most strikingly in flowering times and rates. There were few interactions between ecotype and precipitation, suggesting precipitation is a strong driver of biomass production, whereas adaption of ecotypes to their local environment affects physiological processes. A second experiment studied the response of local populations of P. virgatum to nocturnal warming. Results showed significant differences in daytime E, daytime gs, and flowering phenology between treatments. Differences in aboveground biomass were between topographic positions. I concluded that water availability, based on topographic position, is a strong driver of P. virgatum aboveground biomass production, but nocturnal warming has the potential to impact flowering phenology, physiological responses, and exacerbate plant water stress. I also reviewed the literature on the ecological effects of implementing switchgrass cultivation for biofuel. From the literature review, I concluded that large-scale switchgrass cultivation will have widespread ecological impacts. If landscape heterogeneity is maintained through harvest rotations, no till farming, and mixed species composition, ecosystem services can be maintained while providing economic value.
Keywords: Ecophysiology; Climate change; Biofuel; Grassland; Aboveground biomass; Agronomy (0285); Biology (0306); Ecology (0329)